Biosynthesis, optimization, and characterization of CuNPs using Bacillus licheniformis CPJN13S and their antibacterial activity - Rani, Simran; Dhankher, Shikha; Kumar, Pradeep; Dahiya, Priyanka; Arora, Kiran; Dang, Amita Suneja; Suneja, Pooja (Frontiers in Nanotechnology, 2025)
Nanoparticles (NPs) possess unique properties due to their higher surface-to-volume ratio and reactivity. Negative environmental impact and high cost of traditional modes of synthesis have driven the shift towards utilization of microbes and plants for synthesising NPs, referred as the biological or ‘Green’ synthesis. This study reported extracellular synthesis of copper NPs (CuNPs) using the supernatant of Bacillus licheniformis CPJN13S. The parameters affecting this process were optimized by OFAT approach and were reported to be 5 mM concentration of copper sulfate (CuSO4), 32 h incubation period, 18 h reaction time, 20:20 filtrate/substrate ratio, 7 pH, and 37 °C temperature. CuNPs produced a characteristic UV-Visible absorption peak between 550–650 nm, Z-average of 305.3 nm and zeta potential value of −24.7 mV. SEM and HR-TEM revealed hexagonal shape of NPs having average size of 12.4 nm. XRD peaks obtained at 2θ positions of 45.52°, 56.52°, and 75.34° matched to diffraction from Cu. Antimicrobial assay conducted using 100 μg/mL CuNPs led to highest inhibition of 20.4% (Bacillus subtilis MTCC No. 441) and 43% (Staphylococcus aureus MTCC No. 737), at 21 h and 27 h, respectively. The results suggest that biological synthesis can serve as the eco-friendly alternative of physical and chemical modes of synthesizing CuNPs and can be used to develop highly effective antibacterial agents.